A study based on use of Complementary and Alternative Medicine among Diabetic Patients in Karachi, Pakistan - Kulsoom Jawed; Nighat Nisar; Mehwish Hussain; Faryal Nawab (Journal of the Dow University of Health Sciences, 2019)
Objective: To determine frequency and factors leading to CAM use in diabetic patient visiting tertiary care hospitals in Karachi.